Nasionalisme dan konflik etnis di Indonesia / Jacques Bertrand ; penerjemah, Achmad Munjid ; penyunting, Aditya Pratama - BERTRAND, Jacques; Achmad Munjid; Aditya Pratama (Ombak, 2012)
xxxii, 384 hlm. : ilus. ; 23 cm